CD36 facilitates fatty acid uptake by dynamic palmitoylation-regulated endocytosis - Hao, Jian-Wei; Wang, Juan; Guo, Huiling; Zhao, Yin-Yue; Sun, Hui-Hui; Li, Yi-Fan; Lai, Xiao-Ying; Zhao, Ning; Wang, Xu; Xie, Changchuan; Hong, Lixin; Huang, Xi; et al. (Nature communications, 2020)
Fatty acids (FAs) are essential nutrients, but how they are transported into cells remains unclear. Here, we show that FAs trigger caveolae-dependent CD36 internalization, which in turn delivers FAs into adipocytes. During the process, binding of FAs to CD36 activates its downstream kinase LYN, which phosphorylates DHHC5, the palmitoyl acyltransferase of CD36, at Tyr91 and inactivates it. CD36 then gets depalmitoylated by APT1 and recruits another tyrosine kinase SYK to phosphorylate JNK and VAVs to initiate endocytic uptake of FAs. Blocking CD36 internalization by inhibiting APT1, LYN or SYK abolishes CD36-dependent FA uptake. Restricting CD36 at either palmitoylated or depalmitoylated state eliminates its FA uptake activity, indicating an essential role of dynamic palmitoylation of CD36. Furthermore, blocking endocytosis by targeting LYN or SYK inhibits CD36-dependent lipid droplet growth in adipocytes and high-fat-diet induced weight gain in mice. Our study has uncovered a dynamic palmitoylation-regulated endocytic pathway to take up FAs. The mechanistic details of fatty acid uptake into cells remains poorly understood. Here, the authors identify CD36 internalization via cavaeolae and demonstrate dynamic palmitoylationof CD36 is required for endocytic uptake of fatty acids.